“DEVELOPMENT OF PHYSICAL SKILLS IN VISUALLY IMPAIRED STUDENTS USING GAME-BASED AND SIMULATION METHODS” - Qurbonova Nasiba Mirsalim qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This article explores methods for developing physical skills in visually impaired students through game-based and simulation approaches. The study examines how preparatory classes utilize interactive games and simulation exercises to improve endurance, speed, balance, and coordination. The article emphasizes the importance of individualized instruction and safe practice environments.